Computer assisted retraining of attentional impairments in patients with multiple sclerosis. Issue 4 (1st April 1998) - Plohmann, A M; Kappos, L; Ammann, W; Thordai, A; Wittwer, A; Huber, S; Bellaiche, Y; Lechner-Scott, J
Abstract : OBJECTIVE: To evaluate the efficacy of a computer based retraining of specific impairments of four different attentional domains in patients with multiple sclerosis. METHODS: Twenty two outpatients with multiple sclerosis received consecutively a specific training comprising 12 sessions in each of the two most impaired attention functions. The baseline of attentional deficits, the performance after each training period, and the course of performance in the next nine weeks was assessed by a computerised attention test battery. Additionally, the impact of the training on daily functioning was evaluated with a self rating inventory. RESULTS: Subgroups of patients with multiple sclerosis showing different patterns of attentional impairment could be separated. Significant improvements of performance could almost exclusively be achieved by the specific training programmes. The increase of performance remained stable for at least nine weeks. For quality of life patients reported less attention related problems in everyday situations. CONCLUSIONS: In patients with multiple sclerosis it seems worthwhile to assess attentional functions in detail and to train specific attention impairments selectively.